2014
DOI: 10.1021/pr400803w
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Proteomic Analysis of the Metabolism Mechanism Associated with Silicon Response in the Marine Diatom Thalassiosira pseudonana

Abstract: Silicon is a critical element for diatom growth; however our understanding of the molecular mechanisms involved in intracellular silicon responses are limited. In this study, an iTRAQ-LC-MS/MS quantitative proteomic approach was coupled with an established synchrony technique to reveal the global metabolic silicon-response in the model diatom Thalassiosira pseudonana subject to silicon starvation and readdition. Four samples, which corresponded to the time of silicon starvation, girdle band synthesis, valve fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 77 publications
5
39
0
Order By: Relevance
“…While the correlation between transcript and protein abundance is not absolute 46, 47 , components of protein complexes such as the ribosome or the proteasome generally show a high degree of co-expression 43, 4850 . Frustule synthesis in diatom cultures is strongly correlated with the cell cycle; furthermore, synthesis of the valve and girdle bands is partly separated in time 20, 38, 51 . It is likely that the expression of proteins involved in frustule biosynthesis needs to be coordinated, and that substructures of the frustule need different subsets of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the correlation between transcript and protein abundance is not absolute 46, 47 , components of protein complexes such as the ribosome or the proteasome generally show a high degree of co-expression 43, 4850 . Frustule synthesis in diatom cultures is strongly correlated with the cell cycle; furthermore, synthesis of the valve and girdle bands is partly separated in time 20, 38, 51 . It is likely that the expression of proteins involved in frustule biosynthesis needs to be coordinated, and that substructures of the frustule need different subsets of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed large clusters of genes with expression that is correlated with central Si metabolism genes such as Si transporters or silaffins 35, 36 . Proteomic studies of diatom frustules 16, 37 and responses to Si replenishment 38 have provided another layer of information regarding Si metabolism and frustule synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to acquire a comprehensive and quantitative protein profile, the isobaric tags for relative and absolute quantitation (iTRAQ) has been developed to become an approach appropriate for investigating proteomic changes during various developmental stages [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the labeled peptide mixtures were pooled and pre-separated by strong cation exchange chromatography with the LC-20AB HPLC pump system (Shimadzu, Kyoto, Japan). iTRAQ analysis was performed on a TripleTOF 5600 system (AB SCIEX, Concord, ON, Canada) combined with a Famos autosampler (LC Packings) and LC20-AD Nano HPLC (Shimadzu, Kyoto, Japan), according to a previously reported study (Du et al 2014). Proteome Discoverer software (ver.1.2.0.339; Thermo Fisher Scientific, San Jose, CA, USA) was used to transform raw data files into MGF files.…”
Section: Solexa/illumina Sequencing and Itraq-based Proteome Analysismentioning
confidence: 99%